In vitro combinatory antimicrobial effect of plumbagin with oxacillin and tetracycline against Staphylococcus aureus - Rondevaldova, Johana; Novy, Pavel; Kokoska, Ladislav (PTR. Phytotherapy research, 2015)
Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), a bicyclic naphthoquinone naturally distributed among Plumbago species, has been reported to have antimicrobial activity against a wide range of microorganisms. In this study, plumbagin was examined for its combinatory antimicrobial effect with tetracycline or oxacillin against nine strains of Staphylococcus aureus, including its methicillin- and multidrug-resistant strains. Minimum inhibitory concentrations were determined through the broth microdilution method, whereas the combinatory effect was evaluated according to the sum of fractional inhibitory concentration (ΣFIC) indices. Additive interactions were obtained for both combinations against most of the strains tested. Synergy was obtained for combination with oxacillin against two out of seven strains (ΣFIC range 0.273-0.281), both were methicillin resistant. Our results proved plumbagin as a compound suitable for anti-Staphylococcal combinatory testing. Moreover, to the best of our knowledge, this is the first report of plumbagin synergy with oxacillin against S. aureus strains, including its resistant forms.
Keywords: Microbial Sensitivity Tests; synergismus léků; tetracyklin; Staphylococcus aureus; Tetracycline; Drug Synergism; Oxacillin; naftochinony; mikrobiální testy citlivosti; Anti-Bacterial Agents; antibakteriální látky; mnohočetná bakteriální léková rezistence; Naphthoquinones; oxacilin; Drug Resistance, Multiple, Bacterial